The effect of multiple outgrowths from bronchial tissue explants on progenitor/stem cell number in primary bronchial epithelial cell cultures from smokers and patients with COPD - Bostancieri, Nuray; Bakir, Kemal; Kul, Seval; Eralp, Ayhan; Kayalar, Ozgecan; Konyalilar, Nur; Rajabi, Hadi; Yuncu, Mehmet; Yildirim, Ali Önder; Bayram, Hasan (Frontiers in Medicine, 2023)
Background: Although studies suggest a deficiency in stem cell numbers in chronic airway diseases such as chronic obstructive pulmonary disease (COPD), the role of bronchial epithelial progenitor/stem (P/S) cells is not clear. The objectives of this study were to investigate expression of progenitor/stem (P/S) cell markers, cytokeratin (CK) 5, CK14 and p63 in bronchial epithelial explants and cell cultures obtained from smokers with and without COPD following multiple outgrowths, and to study this effect on bronchial epithelial cell (BEC) proliferation.Methods: Bronchial epithelial explants were dissected from lung explants and cultured on coverslips. Confluent cultures were obtained after 3-4 weeks' (transfer, Tr1), explants were then transferred and cultured for a second (Tr2) and third (Tr3) time, respectively.At each stage, expression of CK5, CK14 and p63 in explants and BEC were determined by immunostaining. In parallel experiments, outgrowing cells from explants were counted after 4wks, and explants subsequently transferred to obtain new cultures for a further 3 times.As the transfer number advanced, CK5, CK14 and p63 expression was decreased in both explants and BEC from both smokers without COPD and patients with COPD, with a more pronounced decrease in BEC numbers in the COPD group. Total cell numbers cultured from explants were decreased with advancing outgrowth number in both groups. Smoking status and lung function parameters were correlated with reduced P/S marker expression and cell numbers.3 Conclusions: Our findings suggest that the number of P/S cells in airway epithelium may play a role in the pathogenesis of COPD, as well as a role in the proliferation of airway epithelial cells, in vitro.